PENERAPAN METODE ISYARAT TANGAN DALAM PEMBELAJARAN MENGHAFAL DAN MENGARTIKAN AL-QUR’AN - Rahmiy kurniasary; Ismail Sukardi; Ahmad Syarifuddin (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2020)
Hand gesture method including requires high memorization ability, some students are not active and focus in synchronizing the pronunciation of lafadz verses and doing hand gestures in learning to memorize and interpret the Qur'an. The purpose of this study was to determine the application of the method of hand gesture in learning to memorize and interpret the Qur'an of students inX garade in Madrasah Aliyah Negeri 1 Prabumulih. The research method used is descriptive qualitative analysis that discusses the application of the method of hand gesture in learning to memorize and interpret the Qur'an of students inX grade in Madrasah Aliyah Negeri 1 Prabumulih. The type of approach used descriptive qualitative with data collection techniques through observation, interviews, documentation and triangulation. Analysis of data qualitatively through three stages, namely data reduction, data presentation and conclusion stages. The results of research conducted by researchers are, first, the steps in the application of hand sign method by the teacher of Al-Qur'an Hadith in X.IPA3 includes teacher activities, namely the teacher explains the material and gives examples of verses to be memorized and interpreted using method of hand gestures on learning video shows on the projector. Student activities, namely students apply the method of hand gesture to the verse that has been taught. Second, supporting factors in the application of hand gesture methods in the form of internal factors, namely from the level of willingness and ability to memorize, external namely in terms of the use of media, teacher skills and a pleasant learning atmosphere. Third, the inhibiting factor in the application of the hand gesture method is the time required by each student, the level of student willingness, skills in making hand gestures and synchronization between the pronunciation of lafadz with hand movements.